2019
DOI: 10.3389/fcell.2019.00242
|View full text |Cite
|
Sign up to set email alerts
|

Naphthoquinone Tryptophan Hybrids: A Promising Small Molecule Scaffold for Mitigating Aggregation of Amyloidogenic Proteins and Peptides

Abstract: A current challenge faced by researchers is the lack of disease-modifying therapeutics for amyloid formation that is associated with several human diseases. Although the monomeric proteins or peptides involved in various amyloidogenic diseases do not have amino acid sequence homology, there appears to be a structural correlation among the amyloid assemblies, which are responsible for distinct pathological conditions. Here, we review our work on Naphthoquinone Tryptophan (NQTrp) hybrids, a small molecule scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 75 publications
1
29
0
Order By: Relevance
“…Tryptophan-coated gold and silver nanoparticles have been shown to inhibit both spontaneous and seed-induced aggregation of insulin 82 . Naphthoquinone-tryptophan hybrids displayed promising potential for mitigating the amyloidogenicity of several proteins and peptides 44,45,83 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tryptophan-coated gold and silver nanoparticles have been shown to inhibit both spontaneous and seed-induced aggregation of insulin 82 . Naphthoquinone-tryptophan hybrids displayed promising potential for mitigating the amyloidogenicity of several proteins and peptides 44,45,83 .…”
Section: Discussionmentioning
confidence: 99%
“…Here we examined this concept by synthesizing tryptophan-galactosylamine hybrid molecules and tested their ability to inhibit the aggregation of Aβ42 and hIAPP. Tryptophan was shown to be highly effective in intercalating the fibrils of various amyloidogenic proteins for inhibiting their aggregations 42 , 44 , 45 , 55 , 56 . Galactose (Gal), one of the most abundant monosaccharide in the human body, plays a vital role in numerous biological processes, modulating and mediating them 57 , 58 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42] The other element of the designed hybrid molecules, NQ, was chosen because quinone exhibitsv arious biological properties and its derivatives, for example NQTrp, were shown to modulate aggregation of several amyloidogenic proteins associated with various proteinopathies, including PD. [27,43,44] The modeo fa ction of NQTrp with an amyloidogenic protein likely occurs through p-p interaction between the aro-matic moiety of Tryptophan anda romatic amino acid of the protein, while the quinone element interferes with the process aggregation, thus resulting in inhibition of amyloid formation. [44][45][46][47] These activities of NQ derivatives and DA prompted us to conjugate them and we hypothesized that the aromatic moiety of DA in the hybrid molecules NQDA and Cl-NQDA will bind the aromatic residues of a-Syn and intercalate within the b-sheets of the protein, whereas the NQ moiety together with the two hydroxyl groups of DA will hindert he a-Syn self-aggregation process to inhibit amyloid formation.…”
Section: Introductionmentioning
confidence: 99%
“…[27,43,44] The modeo fa ction of NQTrp with an amyloidogenic protein likely occurs through p-p interaction between the aro-matic moiety of Tryptophan anda romatic amino acid of the protein, while the quinone element interferes with the process aggregation, thus resulting in inhibition of amyloid formation. [44][45][46][47] These activities of NQ derivatives and DA prompted us to conjugate them and we hypothesized that the aromatic moiety of DA in the hybrid molecules NQDA and Cl-NQDA will bind the aromatic residues of a-Syn and intercalate within the b-sheets of the protein, whereas the NQ moiety together with the two hydroxyl groups of DA will hindert he a-Syn self-aggregation process to inhibit amyloid formation. Ap revious report observed that tyramine, which differs from DA only by a hydrogen replacing ah ydroxyl group, exhibited less inhibitory activity than DA towards a-Syn due to aloss of electrostatic interactions with the two negatively charged groups of the NAC region in a-Syn.…”
Section: Introductionmentioning
confidence: 99%